50 Great Myths About Religions - Morreall, John and Sonn, Tamara (Chichester Wiley Blackwell, 2014)
50 Great Myths about Religions is an intriguing, informative, and often humorous introduction to some of the long standing myths that surround religious belief. This engaging book will get its readers thinking about how and why certain myths have arisen, and their continuing influence on our personal and collective view of religion. Offers a lively, informative, and thought-provoking introduction to some of the common misbeliefs surrounding religions Discusses myths about religious belief in general, as well as specific ideas that surround Judaism, Christianity
Include Index
Keywords: Religion -- Comparative Religion -- Religion Essays